2006
DOI: 10.1152/japplphysiol.01285.2005
|View full text |Cite
|
Sign up to set email alerts
|

Role of nitric oxide in the regulation of digital pulse volume amplitude in humans

Abstract: . Role of nitric oxide in the regulation of digital pulse volume amplitude in humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
322
2
8

Year Published

2008
2008
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 405 publications
(347 citation statements)
references
References 21 publications
15
322
2
8
Order By: Relevance
“…11,12) Because this index mainly reflects NO-dependent vasodilation, 17) our results suggest that one round of stretching exercises increased NO production from vascular endothelial cells in AMI patients. Awolesi, et al showed upregulation of eNOS mRNA expression in bovine vascular endothelial cells subjected to cyclic stretch stimuli for 15 minutes and increased eNOS translation with 24-hour cyclic stretch stimuli.…”
Section: Discussionmentioning
confidence: 72%
“…11,12) Because this index mainly reflects NO-dependent vasodilation, 17) our results suggest that one round of stretching exercises increased NO production from vascular endothelial cells in AMI patients. Awolesi, et al showed upregulation of eNOS mRNA expression in bovine vascular endothelial cells subjected to cyclic stretch stimuli for 15 minutes and increased eNOS translation with 24-hour cyclic stretch stimuli.…”
Section: Discussionmentioning
confidence: 72%
“…The peripheral vascular bed at distal limbs is the major site of sympathetic α-adrenergic vasoconstrictor activity [50,51]. The use of the specific NO antagonist L-NMMA has defined the contribution of NO to these vasomotor responses: Approximately 60% of the PAT response is mediated by NO release [52,53]; the rest is probably mediated by the autonomous nervous system.…”
Section: How Can We Measure Endothelial Function?mentioning
confidence: 99%
“…Recently, finger plethysmography peripheral arterial tonometry has also been used. 42,43 Circulating levels of nitrite/nitrate, cyclic guanosine 3 0 ,5 0 -monophosphate, vascular cell adhesion molecule-1, intracellular adhesion molecule-1, monocyte chemoattractant protein-1, plasminogen activator inhibitor-1, von Willebrand factor, asymmetrical dimethylarginine, endothelial microparticles and progenitor cells are also measured as indices of endothelial function. 21,[44][45][46][47] However, these measurements do not directly reflect the production of NO from endothelial cells and are not 'function' .…”
Section: Endothelial Functionmentioning
confidence: 99%